Organizational Climate and the Effectiveness of a Human Relations Training Program - Hand, Herbert H.; Richards, Max D.; Slocum, John W. (Academy of Management Journal, 1973)
Ninety days after a human relations training program, little change in attitudes and behavior of managers was observed. Eighteen months later, significant positive changes in attitudes existed in the experimental group; negative changes were observed in the control group. The manager?s perception of the organization?s climate moderated these findings.